Problem solving ability pada siswa : bagaimana peran self efficacy - andriani, nadiya; efendy, mamang; pratikto, herlan (Faculty of Psychology Universitas 17 Agustus 1945 Surabaya, 2024)
The objective of this research is to determine the relationship between self efficacy and problem-solving ability among students at SMK PGRI 2 Ponorogo. This study employs a quantitative research method. The population in this study consists of all 11th-grade students at SMK PGRI 2 Ponorogo, totaling 899 students. The participants in this research amount to 315 students, selected using the accidental sampling technique. The data collection instruments in this research include two scales: the problem-solving ability scale and the self efficacy scale. The data analysis technique used is product moment correlation. Based on the results of the data analysis, it is demonstrated that self efficacy has a positive and highly significant correlation with students' problem-solving ability. In conclusion, the hypothesis in this study is accepted. Tujuan dari penelitian ini adalah untuk mengetahui hubungan antara self efficacy dengan problem solving ability pada siswa di SMK PGRI 2 Ponorogo. Penelitian ini menggunakan metode penelitian kuantitatif. Populasi dalam penelitian ini adalah seluruh siswa kelas XI SMK SMK PGRI 2 Ponorogo dengan jumlah 899 siswa. Partisipan dalam penelitian ini berjumlah 315 siswa yang diambil dengan menggunakan teknik accidental sampling. Instrumen pengumpulan data dalam penelitian ini menggunakan dua skala, yaitu skala problem solving ability dan skala self efficacy. Teknik analisis data yang digunakan adalah korelasi product moment. Berdasarkan hasil analisis data dibuktikan bahwa self efficacy berkorelasi positif dan sangat signifikan dengan problem solving ability siswa. Kesimpulannya, hipotesis dalam penelitian ini diterima.